2023
DOI: 10.26444/aaem/158872
|View full text |Cite
|
Sign up to set email alerts
|

Use of neural network based on international classification ICD-10 in patients with head and neck injuries in Lublin Province, Poland, between 2006–2018, as a predictive value of the outcomes of injury sustained

Abstract: Introduction and objective. Head and neck injuries are a heterogeneous group in terms of both clinical course and prognosis. For years, there have been attempts to create an ideal tool to predict the outcomes and severity of injuries. The aim of this study was evaluation of the use of selected artificial intelligence methods for outcome predictions of head and neck injuries. Material sand Method. 6,824 consecutive cases of patients who sustained head and neck injuries, treated in hospitals in the Lublin Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The efficacy of neural networks in medical applications was first demonstrated by Penny and Frost in 1996 [ 26 ], showing potential comparable to clinical reasoning. Recent efforts to apply AI to injury outcome assessment using the International Classification of Diseases highlight the need for nonlinear predictive models [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of neural networks in medical applications was first demonstrated by Penny and Frost in 1996 [ 26 ], showing potential comparable to clinical reasoning. Recent efforts to apply AI to injury outcome assessment using the International Classification of Diseases highlight the need for nonlinear predictive models [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of numerical, statistical, and machine-learning methods can complement typical experimental studies and may allow a better understanding of the complex relationships commonly found in medicine [20][21][22][23]. Statistical analyses based on the ICD-10 classification are particularly useful in trauma research because they allow the classification and comparison of different types of injuries and their prevalence in the population [24].…”
Section: Introductionmentioning
confidence: 99%